William Horner Andrews (1887-1953)- first professor of physiology at Onderstepoort - Verwoerd, D W; Andrews, W J H (Journal of the South African Veterinary Association, 2011)
W H Andrews qualified as a veterinarian in London in 1908 and was recruited soon after, in 1909, by Sir Arnold Theiler to join the staff of the newly established veterinary laboratory at Onderstepoort. After initial studies on the treatment of trypanosomosis and on snake venoms he was deployed by Theiler in 1911 to start research on lamsiekte (botulism)at a field station on the farm Kaffraria near Christiana, where he met and married his wife Doris. After a stint as Captain in the SA Veterinary Corps during World War I he succeeded D T Mitchell as head of the Allerton Laboratory in 1918, where he excelled in research on toxic plants, inter alia identifying Matricaria nigellaefolia as the cause of staggers in cattle. When the Faculty of Veterinary Science was established in 1920 he was appointed as the first Professor of Physiology. After the graduation of the first class in 1924, and due to health problems, he returned to the UK, first to the Royal Veterinary College and then to the Weybridge Veterinary Laboratories of which he became Director in 1927. After his retirement in 1947 he returned to South Africa as a guest worker at Onderstepoort where he again became involved in teaching physiology when Prof. Quin unexpectedly died in 1950. Andrews died in Pretoria in 1953 and was buried in the Rebecca Street Cemetery.